Studies on the enzymatic specificity of diguanylate cyclases domains and the production of new second messengers - Justo Arevalo, Santiago (2022)
In the first chapter, studies on substrate recognition and enzymatic activity of GGDEF domains are presented. Many proteins containing GGDEF domains are diguanylate cyclases (DGCs, EC 2.7.7.65), enzymes that catalyze the conversion of 2 GTP molecules into the second messenger c-di-GMP in prokaryotes. This molecule is primarily implicated in the transition between motile and sessile lifestyles, as well several other phenotypes. Redundancy and diversity of GGDEF domain sequences in many bacterial genomes raises the possibility that other enzymatic functions may yet be discovered. To test this hypothesis, i) the effect of point mutations on the structure and enzymatic activity of GGDEF domains is analyzed, ii) the enzymatic specificity of wild-type GGDEF domains from different proteins is also tested, and iii) when non-canonical products are detected, enzymatic models are studied to understand its preferential production. The principal results obtained from these studies are as follows. Seven mutants of the DGC PleD (a GGDEF containing-protein from Caulobacter crescentus) were constructed and the crystallographic structure of two of them was solved, showing that they are unlikely to bind the guanine moiety in its active site. Additionally, five mutants of XAC0610, another DGC from Xanthomonas citr, were constructed and their substrate specificities were evaluated. None of those mutants were able to use ATP as a substrate. Finally, seven different GGDEF domain-containing DGCs from different sources were expressed and purified and their enzymatic specificities were tested with several nucleotide triphosphates. One enzyme, GSU1658 from Geobacter sulfurreducens was particularly promiscuous and shown to produce c-di-GMP, c-di-AMP, c-di-IMP, c-di-2´dGMP, cGAMP, c-GIMP, and c-AIMP. Interestingly, XAC0610 was able to recognize 2´dGTP as substrate. Analysis of enzyme kinetics of XAC0610 in presence of 2´dGTP and/or GTP showed the preferential formation of the hybrid linear product pppGp2´dG. The second chapter present studies on cyanide metabolism in Bacillus with focus on the cyanide dihydratase of Bacillus safensis. Cyanide is widely used in industries due to its high affinity for metals. This same ability confers potent toxicity to this compound. Thus, industries must reduce the cyanide concentration from wastewater before its final disposal. Physical, chemical, and biological methods have been developed to achieve this goal, but knowledge about metabolic pathways and the biology of enzymes involved in cyanide degradation is still scarce. Here, the isolation of a Bacillus safensis strain from mine tailings in Peru is described. Classification of this strain was done through a comparative analysis of 132 core genomes of strains from the Bacillus pumilus group. Sequence analysis determined that a cyanide dihydratase (CynD, EC 3.5.5.1)) encoded in the genome of the isolated strain was likely the enzyme responsible for cyanide degradation. Confirmation of the cyanide degrading activity of CynD from this strain was achieved by cloning, expression and purification of the enzyme and its enzymatic characterization. CynD from this strain was active up to pH 9 and oligomerization patterns analyzed by SEC-MALS and electron microscopy showed that the enzyme forms large helical structures at pH 8 and smaller structures at higher pHs. Finally, we show that CynD expression is strongly induced in the presence of cyanide. The last two years of graduate studies were carried out in the context of the COVID-19 pandemic. Thanks to the large amount of publicly available genomic data, we were able to carry out studies on the worldwide dynamics of the spread of SARS-CoV-2 mutants forms. In the first year of the pandemic, genomic classification of 171,461 genomes showed the presence of five major haplotypes based on nine mutations. The worldwide distribution and the temporal evolution of frequency of these haplotypes was carefully analyzed. All the haplotypes were identified in the six regions analyzed (South America, North America, Europe, Asia, Africa, and Oceania); however, the frequency of each of them was different in each of these regions. As of September 30, 2020, haplotype 3 (or operational taxonomic unit 3, OTU_3) was the most prevalent in four regions (South America, Asia, Africa, and Oceania). OTU_5 was the most prevalent in North America and OTU_2 in Europe. Temporal dynamics of the haplotypes showed that OTU_1 became nearly extinct after 8 months of pandemic (November 2020). Other OTUs are still present in different frequencies all around the world, while currently generating new variants. Based on their temporal dynamics, a classification scheme of 115 SARS-CoV-2 mutations identified from 1,058,020 SARS-COV-2 genomes was also performed. Three types of temporal dynamics of mutations were identified: i) High-Frequency mutations are characterized by a rapid increase in frequency upon its appearance, ii) medium and iii) low-frequency mutations maintain mid or low-frequencies for several months and can be region-specific. Finally, we performed a correlation analysis of the effective reproduction number (Rt) of SARS-CoV-2 harboring the high-frequency mutation N501Y with the level of control measures adopted in specific jurisdictions. We show that Rt is negatively correlated with the level of control measures in eight of the nine countries analyzed. This negative correlation was similar when we analyzed the Rt of SARS-CoV-2 not-harboring N501Y. Thus, the control measures likely diminish the Rt of both SARSCoV-2 wild-type and N501Y.